Viscous relaxation of grain‐scale pressure variations. (25th July 2015) - Dabrowski, M.; Powell, R.; Podladchikov, Y.
Abstract In the presence of grain‐scale pressure variations, there will be a natural tendency for deformation to flatten pressure gradients to establish pressure equilibrium. We explore the time‐scale of the survival of pressure variations in the presence of power‐law creep. Such viscous relaxation turns out to be strongly dependent on the exponent in the power‐law creep constitutive relation. For larger exponents, there is the possibility of maintaining pressure variations for the order of a million years, orders of magnitude longer than the viscoelastic relaxation time that is commonly used as a proxy for the pressure relaxation time. Petrologically, this means that while pressure variations may only be transient, their effect may contribute to mineral textural development, even if not preserved in mineral assemblages and mineral compositions.